Success Indicators for Selfbuild Houses in two Ghanaian Cities (Journal of Science and Technology, 2016)
The recognition of success criteria for effective design and construction management purposes has been a topical issue in the housing construction industry for quite a while now. Yet, little is still known of the success indicators for SelfBuild houses, although these constitute the dominant mode of housing supply in many developing countries such as Ghana. To this effect, structured questionnaires were used to elicit from homeowners in two Ghanaian cities the importance they attach to a number of variables as determinants of success for Selfbuild houses, and the data analyzed using scale ranking and one-sample t-test. The analyses revealed that; adequate ventilation for thermal comfort (ranked no. 1), health and safety in the home (ranked no.2), quality of materials (ranked no. 3), quality of workmanship (ranked no. 4) and adequate daylight into rooms ranked (no. 5) are the main determinants of success in Selfbuild houses. The criteria cost and time received the lowest rankings of 10th and 11threspectively suggesting that while these traditional measures could be very important, in the long term they are not issues that Selfbuild homeowners might be particularly concerned about. The findings especially those relating to ventilation, health and safety in the home, quality of materials and adequate daylight are critical for dissemination to all construction professionals/practitioners regarding design decisions and choice of construction materials for Selfbuild houses in a tropical country like Ghana.